Liquidity Risk And Basel III Implementation In Southeast Asia Banking - Nanang Shonhadji; Soni Agus Irwandi (Universitas Muhammadiyah Malang, 2023)
Purpose: The objective of this study was to determine the effect of liquidity coverage ratio, net stable funding ratio, net interest margin, and cost of funds on return on assets in Southeast Asian countries' banking services. Methodology/approach: This research was a quantitative research method. Secondary data was used and collected from stock exchanges in each country. Samples were banks in Indonesia, Malaysia, Cambodia, Philippines, Singapore and Thailand. The data testing technique uses multiple linear regression analysis. Findings: The study inform that net stable funding ratio, liquidity coverage ratio, net interest margin and cost of funds have a significant effect on return on assets. Practical implications: The practical implications were BASEL III implementation to manage liquidity risk and capital in each country have successfully and encourage compliance with bank liquidity and capital aspects according to the framework of BASEL III to enhance the financial performance of banks in Southeast Asian countries. Originality/value: Research on the application of BASEL III in Southeast Asian Countries as a framework that establishes international standards for bank capital adequacy, stress testing, and liquidity requirements is the originality of this research.